PELATIHAN TOEFL PREPARATION PADA SISWA SMA N 1 SECANGGANG - Hassan, Muhammad; Ginting, Donny Adiatmana; De Napoli, Fernando; Mala Sari, Bintang Mala Sari (LPPM STKIP AL MAKSUM, 2024)
The English language ability test, in this case TOEFL, is an international standard language test to measure English language skills for speakers whose mother tongue is not English. In Indonesia, there are several conditions that require someone to take the TOEFL test, including continuing higher education both at home and abroad, meeting college graduation requirements, knowing the level of language skills applying for jobs, and getting a promotion. In general, there are three types of TOEFL, namely IBT (internet-based test), PBT (paper-based test), and ITP (Institutional Testing Program). In this regard, school age is considered the right time to introduce the TOEFL test to students, especially those whose solution is to provide TOEFL PREPARATION training. From the TOEFL training activities carried out from April 15 2024, the results showed that there was a significant increase in the students' TOEFL scores before and after the activity